Italian nursing students' attitudes towards care of the dying patient: A multi-center descriptive study. (September 2021) - Mastroianni, Chiara; Marchetti, Anna; D'Angelo, Daniela; Artico, Marco; Giannarelli, Diana; Magna, Elisa; Motta, Paolo Carlo; Piredda, Michela; Casale, Giuseppe; De Marinis, Maria Grazia
Abstract: Background: International literature reports that nursing students feel unprepared when facing patients and families within dying care. They consider their curricula inadequate in teaching end-of-life care and promoting the attitudes required to care for dying patients. Findings of recent studies exploring nursing students' attitudes towards care of the dying patient are often contradictory. Objectives: To explore Italian nursing students' attitudes towards caring for dying patients. Design: A multicenter cross-sectional study was conducted. Settings: The Bachelor's Degree in Nursing courses of four Universities of the Lazio Region. Participants: The sample included 1193 students. Methods: Data were collected between September 2017 and March 2018 using the Italian version of FATCOD-B-I. The differences between the mean scores were compared through t -test or ANOVA. Associations between scores and participant characteristics were evaluated through generalized linear regression. Results: The mean score of FATCOD-B-I was 115.3 (SD = 9.1). Higher scores were significantly associated with training in palliative care ( p < 0.0001) and experience with terminally ill patients (p < 0.0001). Students manifested more negative attitudes when they perceived patients losing hope of recovering, and patient's family members interfering with health professionals' work. Uncertainties emerged around knowledge of opioid drugs, decision-making, concepts of death and dying, management of mourning, and relational aspects of patient care. Conclusions: Italian nursing students seem to have more positive attitudes towards care of dying patients than most other countries. They believe that caring for a terminal patient is a formative, useful experience but they do not feel adequately prepared in practice. Deeper palliative care education, integrated with practical training, would prepare students better, enabling them to discover their own human and professional capacity to relieve suffering. Highlights: Italian nursing students have more positive attitudes than those of other countries. For Italian nursing students, the experience with dying patients is formative. Education and experience can model and transform students' attitudes. Students do not feel adequately prepared to deal with end-of-life care. Palliative care education is needed to prepare students to empathize with patients.